THE INFLUENCE OF LEADERSHIP, WORK ENVIRONMENT, AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE WITH COMPETENCE AS AN INTERVENING VARIABLE AT SMP BANGUN INSAN MANDIRI MEDAN - Muhammad Amir Sodik; Yohny Anwar (Yayasan Multidimensi Kreatif, 2025)
This study investigates the influence of leadership, work environment, and job satisfaction on employee performance, with competence serving as an intervening variable at SMP Bangun Insan Mandiri Medan. Employing a quantitative research approach and Partial Least Square-Structural Equation Modeling (PLS-SEM) for data analysis, the research involved 190 employees as respondents. The findings reveal that leadership, work environment, and job satisfaction significantly affect employee performance, both directly and indirectly, with competence acting as a partial mediator. Leadership and work environment demonstrated the strongest positive impact on competence, which in turn significantly enhances employee performance. However, job satisfaction showed a weaker influence on competence, though it directly contributes to performance outcomes. The study confirms the critical role of competence in bridging organizational climate variables and performance. These results suggest that to improve employee performance sustainably, educational institutions must invest in developing leadership quality, fostering a supportive work environment, enhancing job satisfaction, and systematically building employee competence. The research contributes to strategic human resource management by integrating empirical evidence into a theoretical framework applicable to the education sector.